Rivaroxaban compared with warfarin in patients with atrial fibrillation and previous stroke or transient ischaemic attack: a subgroup analysis of ROCKET AF - Hankey, Graeme; Hacke, Werner (The lancet, 2012)
Background In ROCKET AF, rivaroxaban was non-inferior to adjusted-dose warfarin in preventing stroke or systemic embolism among patients with atrial ﬁbrillation (AF). We aimed to investigate whether the eﬃcacy and safety of rivaroxaban compared with warfarin is consistent among the subgroups of patients with and without previous stroke or transient ischaemic attack (TIA).